The Relationship Between Cyberbullying And Das Levels (Depression, Anxiety, Stress) Among Adolescents In Salatiga - Desi, Desi; Laetare, Ema Tri (Jurnal Kesehatan Manarang, 2025)
Cyberbullying is a form of bullying that commonly affects adolescents. One of the psychological impacts experienced by victims of cyberbullying includes depression, anxiety, and stress. This study aimed to examine the relationship between cyberbullying and levels of depression, anxiety, and stress (DAS) among adolescents in Salatiga City. A quantitative method with a descriptive correlational approach was used. Data were collected using two stages of questionnaires: the first was the Olweus Bully/Victim Questionnaire-Revised Version (OBVQ-R) to assess exposure to cyberbullying, and the second was the Depression, Anxiety, Stress Scale 42 (DASS-42) to measure psychological symptoms. A total of 151 adolescents participated in the study, conducted from January 17–29, 2024. Statistical analysis using the Chi-Square test showed significant relationships between cyberbullying and depression (p = 0.000), anxiety (p = 0.001), and stress (p = 0.000). Conclusion: Cyberbullying is associated with varying levels of depression, anxiety, and stress in victims. Due to its persistent and hard-to-avoid nature, it causes significant emotional distress among affected adolescents.